SISTEM INFORMASI ADMINISTRASI PEMBUATAN SURAT IZIN MENGEMUDI (SIM) PADA KANTOR KEPOLISIAN REPUBLIK INDONESIA SEKTOR (POLSEK) PASAMAN DENGAN MENGGUNAKAN BAHASA PEMOGRAMAN JAV - Putri Anggraini; Dio Prima Mulya (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2019)
Existing data processing at the Police Station of the Republic of Indonesia Resort (POLRES) Pasaman is still much done manually whether it is recording, storage and retrieval of administrative data making a driver's license when necessary. So to check or find the necessary data, must first disassemble the archives in the data storage cabinet where this will take a long time. Here the authors analyze and design the information system infrastructure that will and should be built, the navigation structure, the database used, the programming language used and the integration of both. For that in making this driver's license is the author using java programming language. From the results of this study, it can be concluded that the process of making a driver's license is well computerized.